Alterações neuromusculares em modelos animais de disfunção colinérgica e sua relação com as Síndromes Miastênicas Congênitas - Matheus Proença Simão Magalhães Gomes (2018)
In mammals, muscle activity is dependent on acetylcholine (ACh) release from neuromuscular junctions (NMJs), and changes with the cholinergic neurotransmission are associated with a variety of neuromuscular disorders, including congenital myasthenic syndromes (CMS). The storage and release of ACh depends on the activity of the Vesicular Acetylcholine Transporter (VAChT), whose loss of function mutations was recently shown to cause human congenital myasthenia. However, long-term consequences of VAChT loss or gain of function for the integrity of motor units and skeletal muscles are unknown. In this study, we examined the motor units in a mouse line with increased VAChT expression, the ChAT-ChR2-EYFP, which show 3x more VAChT expression than control. We also evaluated the skeletal muscles of a mouse model used to study CMS, the VAChT KDHOM, presenting 65% reduction in VAChT expression, reduced ACh release and pronounced muscle weakness. Using the ChAT-ChR2-EYFP mice, we evaluated the morphology of motoneurons, structural and functional parameters of the (NMJs), the morphology of muscle fibers, fiber type (myosin heavy chain isoforms). In addition, we analyzed mice motor function. With the VAChT KDHOM mice, we assessed structural parameters of different skeletal muscles varying the expression of the MyHC, the gastrocnemius, Extensor Digitorum Longus (EDL) and soleus, We also evaluated the fiber type composition and expression of muscle-related genes in the (EDL) and soleus muscles. The performance of VAChT KDHOM mice was also assessed in a physical capacity test. Our results showed changes with the size of motoneurons in the ChAT-ChR2-EYFP mice, together with alterations with synaptic vesicle recycling, ACh release and structure of NMJs. We also verified morphofunctional changes with skeletal muslces and mice motor function. In relation to the VAChT KDHOM mice our analysis revealed that while muscle fibers atrophy in the EDL, they hypertrophy in the soleus muscle of KDHOM mice. Along with this cellular changes, skeletal muscles exhibited altered levels of markers for myogenesis (Pax-7, Myogenin, and MyoD), oxidative metabolism (PGC1-α and MTND1), and protein degradation (Atrogin1 and MuRF1). These findings reveal that physiological cholinergic activity is important to maintain the structure of motor units and that increasing or reducing VAChT expression, and consequently ACh release, significantly impacts either the structure of the components of motor units as well as mice functional parameters.